Efek Mediasi Kepuasan Mahasiswa pada Pengaruh Citra Institusi Terhadap Loyalitas Mahasiswa di Perguruan Tinggi - Hukama, La Diadhan (Nusa Putra University, 2024)
Loyalty in the context of higher education can be described as students' willingness to promote the university to others or return to the university to continue their studies. Student loyalty is directly related to student satisfaction and the image of the educational institution. Student loyalty, institutional image and student satisfaction make important factors that are of concern to higher education managers. In this context, this research was conducted. This study aims to look at the effect of institutional image and student satisfaction on student loyalty with the object of research of students of the Faculty of Economics and Business at one of the private universities in Jakarta. Most of the data utilized in this study are data collected through surveys so that this research is classified as quantitative research and as many as 141 respondents participated in this study. This study succeeded in proving that institutional image has a positive effect on student satisfaction and student satisfaction has a positive effect on student loyalty. Another finding is that research has not been able to prove the effect of institutional image on student loyalty. In addition, this study succeeded in proving the mediating role of student satisfaction on the effect of institutional image on student loyalty